Effect of nitrate on residual nitrite decomposition rate in cooked cured pork. (July 2017) - Waga, Masahiro; Takeda, Shiro; Sakata, Ryoichi
Abstract: The effects of nitrate on the color stability of cooked cured pork were examined. Nitrate inhibited the nitrite decrement and discoloration in the cooked cured ham. Nitrate reduction and nitrite accumulation were observed in the uncooked sausage models, but were not detected in the sausage models cooked at 75 °C. The kinetics of nitrite degradation was subsequently examined at various concentrations of nitric acid at constant acidity. The degradation rate of nitrite was clearly found to decrease with nitric acid content. Thus, nitrate does not appear to serve as a donor of nitrite, but rather inhibits nitrite reduction in cooked meat products, with consequent prolongation of color stability.